IMPLEMENTASI KONSEP INDUSTRIAL PADA SITE TABLE DENGAN PEMANFAATAN LIMBAH DI PT VIGOR JAYA PERKASA - Prasiska Damastuti; Sekar Della Nelia (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2025)
Side table is one of the complementary furniture in the family room, living room, bedroom or other rooms. Side table products in a room are not only considered in terms of their function to place items but also need to be considered in terms of their suitability with the concept of the room. Currently, the industrial housing concept is quite popular with the public, as well as the complementary furniture in it. The implementation of the industrial concept in furniture products is carried out by utilizing a combination of quality materials, creating a warm, unique, and functional atmosphere in the residence. Based on various aspects of design considerations, the design of the side table with an industrial concept was carried out using the design thinking method which includes the stages of empathize, define, ideate, prototype, and test.The design of the side table design with an industrial concept uses waste materials available in the PT Vigor Jaya Perkasa industry. At PT Vigor Jaya Perkasa there are various types of waste that can be utilized such as hollow iron, metal , solid wood, artificial boards, HPL, and veneer. The use of waste materials at PT Jaya Vigor Perkasa in making side tables can be an alternative to increase the selling value of waste. By utilizing a combination of these waste materials, it is hoped that it can show the implementation of the industrial concept in side table furniture products.